The object as Adverb of Manner and the object as adverb of place and time in the book Poetry of Hamedan and its news in pre-Islamic times and Islam - the category of gender (masculine and feminine) by choice - Hassan siwan, Nedal; Rasin Sahn, Prof. Dr. Ahamad (Basra studies journal, 2023)
The research refers to (the object in it (adverb of place and time), and the object for it is an applied study of texts of poetry. The other effects, the study of the research is in two parts: the first: in the saying of the masculine and the feminine in language and idiomatically among linguists and grammarians. The subject of the study was ((Hamdan’s poetry and its news in pre-Islam and Islam period). The researchers collected all the poetic texts that include the masculine and the feminine. As for the methodology of the study in writing the research, it is the (descriptive) approach in an inductive and analytical study of the object in it, and tracking the use of the verbs within the sentence